Epidemiological trends and disease burden of Hodgkin's lymphoma in China from 1990 to 2019 - Wen-Tao WU; Da-Ning LI; Shuai ZHENG; Feng-Shuo XU; Di-Di HAN; Jun LYU (Yixue xinzhi zazhi)
Objective To analyze the epidemiological trends and disease burden of Hodgkin's lymphoma in China from 1990 to 2019. Methods Based on data from the Global Burden of Disease 2019 survey (GBD 2019), we used incidence, mortality, disability-adjusted life years (DALY), years of life lost (YLL) and years lived with disability (YLD) and their standardized rates to analyze the epidemic trends and disease burden of Hodgkin's lymphoma in China from 1990 to 2019. Results From 1990 to 2019, the number of new cases of Hodgkin's lymphoma in China increased from 6,600 to 9,500, an increase of 42.68%, and the overall standardized incidence rate decreased from 0.65/100,000 to 0.57/100,000, a decrease of 11.12%, but it has rebounded since 2006. The number of deaths and standardized mortality rate decreased by 45.30% and 72.00%, respectively. The standardized rate of YLD increased by 66.77%, while standard-ized rates of DALY and YLL showed a decreasing trend of 73.31% and 74.82%, respectively. The incidence, mortality and DALY rates of different genders in-creased with age, but the incidence, mortality and DALY rates of males were higher than those of females. Conclusion From 1990 to 2019, the incidence rate of Hodgkin's lymphoma in China first decreased and then increased, the mortality rate and DALY rate showed a decreasing trend. Men and the elderly remain at high risk of the current disease burden of Hodgkin's lymphoma.